Legal Analysis of Food and Drug Supervision by BPOM from a Health Law Perspective - F.Ramadhan; M.Hidayat (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: The Indonesian Food and Drug Authority (BPOM) plays a pivotal role in public health safety, yet institutional overlapping and enforcement gaps persist within the modern legislative framework. This study examines the legal mechanisms of BPOM from a health law perspective to assess its structural efficacy. Methods: Utilizing a normative juridical legal research methodology, this study analyzes primary and secondary legal materials, including Law No. 17 of 2023 on Health and relevant presidential regulations, through statutory and conceptual approaches. Results: The findings reveal that while BPOM possesses extensive administrative authority, its preventive and repressive supervision is frequently hindered by jurisdictional friction with the Ministry of Health and a lack of independent prosecutorial powers. Discussion: The discussion evaluates these legal gaps against contemporary health law principles, highlighting how the integration of public health mandates and administrative sanctions fails to deter systemic violations by distribution industries. It further integrates a comprehensive literature review on regulatory compliance theory to demonstrate that BPOM requires strengthened constitutional positioning and clear institutional boundaries to eliminate regulatory redundancy. Conclusions: This study concludes that the existing legal framework inadequately supports BPOM’s supervisory mandate, requiring urgent legislative amendments to grant independent enforcement authority and harmonize inter-agency roles to ensure absolute public health protection.